2016
DOI: 10.1080/14756366.2016.1178735
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of inhibition of human glucose 6-phosphate dehydrogenase by some 99mTc chelators byin silicoandin vitromethods

Abstract: The inhibitory effects of methoxyisobutylisonitrile (MIBI), diethylene triamine pentaacetic acid (DTPA), dimercaptosuccinic acid (DMSA) and metilendifosfonat (MDP) on human erythrocyte glucose 6-phosphate dehydrogenase (hG6PD) activity were investigated. For this purpose, hG6PD was initially purified 557-fold at a yield of 51.43% using 2 0 ,5 0 -adenosine diphosphate (ADP) sepharose 4B affinity gel chromatography. The in vitro effects of these chelators on hG6PD enzyme were studied. IC 50 values of MIBI, DTPA,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Considering that G6PD usually only operates around 2% of its maximum potential in non-transformed cells [ 58 ] while in cancer cells this percentage is significantly higher, it is vital to highlight the key role of G6PD in the proliferation of tumor cells. Indeed, several other studies in various tissues also demonstrated the importance of G6PD in cell viability [ 10 , 45 , 59 ].…”
Section: Discussionmentioning
confidence: 93%
“…Considering that G6PD usually only operates around 2% of its maximum potential in non-transformed cells [ 58 ] while in cancer cells this percentage is significantly higher, it is vital to highlight the key role of G6PD in the proliferation of tumor cells. Indeed, several other studies in various tissues also demonstrated the importance of G6PD in cell viability [ 10 , 45 , 59 ].…”
Section: Discussionmentioning
confidence: 93%
“…Interaction between the compound and Phe171 may lead to inhibition of the enzyme by interfering with the interaction between the residue and the substrate. Several G6PDs have demonstrated similar modes of interaction [58,59]. On the other hand, the binding modes showed that compound 52 with the 4-nitrobenzylidene group may inhibit the enzyme by closely interacting with Glu151 residue.…”
Section: Targetsmentioning
confidence: 99%